PENTINGNYA PERANAN INTERNET DALAM DISTRIBUSI PEMASARAN PRODUK UMKM - Deasy Kartikasari (ITB Swadharma, 2021)
Internet technology has created a new gateway in today's business landscape, Thomas L. Friedman revealed that the world today seems to be like a